2015
DOI: 10.1021/acsnano.5b01239
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Flat Bands near the Fermi Level in Epitaxial Rhombohedral Multilayer Graphene

Abstract: The stacking order of multilayer graphene has a profound influence on its electronic properties. In particular, it has been predicted that a rhombohedral stacking sequence displays a very flat conducting surface state: the longer the sequence, the flatter the band. In such a flat band, the role of electron-electron correlation is enhanced, possibly resulting in high Tc superconductivity, magnetic order, or charge density wave order. Here we demonstrate that rhombohedral multilayers are easily obtained by epita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 29 publications
5
102
1
Order By: Relevance
“…23−25 Experimental signatures of these flat bands has been recently observed in scanning tunnelling spectroscopy (STS) and angular-resolved photo emission spectroscopy (ARPES) investigations of nanometer scale domains of ABC-stacked graphene multilayers (5 layers) grown on 3C-SiC. 26 In this Letter, we demonstrate, using Raman scattering techniques, that ABC-stacked multilayers (N > 5) can be found within exfoliated N-LG flakes. They have characteristic signatures in their Raman scattering response, which allow for their identification at room temperature.…”
mentioning
confidence: 69%
“…23−25 Experimental signatures of these flat bands has been recently observed in scanning tunnelling spectroscopy (STS) and angular-resolved photo emission spectroscopy (ARPES) investigations of nanometer scale domains of ABC-stacked graphene multilayers (5 layers) grown on 3C-SiC. 26 In this Letter, we demonstrate, using Raman scattering techniques, that ABC-stacked multilayers (N > 5) can be found within exfoliated N-LG flakes. They have characteristic signatures in their Raman scattering response, which allow for their identification at room temperature.…”
mentioning
confidence: 69%
“…The projection of the spiral to the top or bottom surface of graphite determines the boundary of the (approximate) surface flat band [8,9]. This flattening of the spectrum has been recently observed in epitaxial rhombohedral multilayer graphene [11].…”
Section: Introductionmentioning
confidence: 77%
“…This view is supported be related studies that have shown explicitly that a wider unit cell inŷ-direction does not give raise to relevant additional effects 15 . In experiments multilayer graphene is not always nicely stacked and hence predicting sliding patterns in practice is difficult 25 . Moreover, we considered only cases where bending was parallel either to armchair-or to zigzagdirection.…”
Section: Discussionmentioning
confidence: 99%